2018
DOI: 10.21037/tcr.2017.11.10
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of breast lymphoma: a single-institution retrospective analysis

Abstract: Background: Breast lymphoma (BL) is a rare entity. Although mimicking clinical presentation and radiological features of epithelial breast malignancies, prognosis and treatment management are different. Here we report our single institution experience in such population. Methods: The database of our pathology institute was retrospectively searched for breast neoplasms coded as lymphoma from January 2000 to January 2017. The assessed data were: gender, age at diagnosis, laterality, stage (primary or secondary),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(53 reference statements)
3
5
0
Order By: Relevance
“…Regardless of its category, the clinical presentation of BL, which usually includes breast mass with or without enlarged ipsilateral axillary lymph node, is very similar to BC. Previous case series reported a wide variety of histologic subtypes, with the most common ones being DLBCL, MALT lymphoma, and follicular lymphoma 4‐12 . Our study showed similar results with the previous series as DLBCL, MALT lymphoma, and follicular lymphoma constituted in most cases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regardless of its category, the clinical presentation of BL, which usually includes breast mass with or without enlarged ipsilateral axillary lymph node, is very similar to BC. Previous case series reported a wide variety of histologic subtypes, with the most common ones being DLBCL, MALT lymphoma, and follicular lymphoma 4‐12 . Our study showed similar results with the previous series as DLBCL, MALT lymphoma, and follicular lymphoma constituted in most cases.…”
Section: Discussionsupporting
confidence: 90%
“…ones being DLBCL, MALT lymphoma, and follicular lymphoma. [4][5][6][7][8][9][10][11][12] Our study showed similar results with the previous series as DLBCL, MALT lymphoma, and follicular lymphoma constituted in most cases.…”
Section: Discussionsupporting
confidence: 87%
“…A range of 5-year overall survival rate for primary breast lymphoma has been reported from 49 to 67% [43]. Moreover, 5-year survival rates in breast lymphoma were estimated 77% [44]. According to these explanations, the lowest survival rate estimated in the "other cancers" group can be justified.…”
Section: Survival Based On Pathological Typementioning
confidence: 98%
“…Primary breast lymphoma (PBL); is defined as a malignant lymphoma primarily involving the breast in the absence of previously detected lymphoma localizations. SBL is defined by the presence of secondary involvement of breast tissue by a concurrent or previous systemic lymphoma and is more common than PBLs [2][3][4][5][6][7]. PBL is characterized by primary degeneration of the breast lymphoid tissue with or without damage to the lymph nodes in the drainage area.…”
Section: Introductionmentioning
confidence: 99%
“…PBL is characterized by primary degeneration of the breast lymphoid tissue with or without damage to the lymph nodes in the drainage area. In 1972, Wiseman and Liao defined PBL on the basis of three precise criteria: (1) Presence of mammary glandular tissue in the middle of the lymphomatous infiltrate or in its direct contact, detected by a good quality sample; (2) The absence of systemic metastases in the extension assessment; (3) The absence of a history of extra mammary lymphoma. [8].…”
Section: Introductionmentioning
confidence: 99%